Kekerasan Jarak Jauh melalui Penyalahgunaan Identitas pada Aplikasi Online: Analisis Viktimologi terhadap Perlindungan Korban - Raisya Aliya Putri; Salsabila Raisah Saputri; Nanda Zahra Sausan; Anindya Maheswari; Annisa Hamida Rahman; Ahnaf Dzul Hazmi (Universitas Sultan Ageng Tirtayasa, 2026)
The expansion of digital technology has not only reshaped communication patterns but also facilitated the emergence of new forms of violence, particularly those conducted remotely through identity misuse on online platforms. This study seeks to examine the patterns of such violence and evaluate the extent to which legal frameworks in Indonesia provide adequate protection for victims from a victimological standpoint. This research applies a qualitative method with an empirical juridical approach, utilizing primary data obtained from in-depth interviews with a victim of identity misuse, supported by secondary sources including legislation and scholarly literature. The findings reveal that perpetrators frequently exploit personal relationships and access to victims’ private data to conduct harmful actions, such as creating fraudulent accounts that damage victims’ reputation and safety. The consequences experienced by victims are not only material but also extend to psychological distress, social marginalization, and ongoing insecurity. Additionally, a significant number of cases remain unreported due to procedural difficulties, lack of trust in law enforcement, prolonged legal processes, and the risk of further victimization. Although regulatory instruments such as cyber law and sexual violence legislation provide a legal basis, their practical implementation is often inadequate in addressing the urgency and complexity of digital-based crimes. Therefore, this study highlights the necessity of strengthening victim-centered legal protection, enhancing institutional responsiveness, and establishing rapid intervention mechanisms to ensure effective victim protection in the digital environment.